Health Impact of Domestic Violence Cases During Covid-19 Pandemic: The Case Study in Malang Regency of East Java - Suryani,; Atik Triratnawati, (Indonesian Journal of Medical Anthropology, 2021)
The impact of Covid-19 has not only affected the health sector but also economic and social sectors. In the social sector, the increase of domestic violence cases is being concern. It has a wide impact towards women’s health. This paper wants to reveal the impact of women’s health including reproductive health suffered by domestic violence victims and how they find solutions to the problems they face. Data collection was using ethnographic research methods from April to June 2021 in Malang regency. Observations and interviews were conducted towards 5 domestic violence victims and 2 associate staffs of domestic violence victims. Data analysis was carried out by classifying the data with the classification of minor, severe and reproductive health impacts. As a result, researcher found that domestic violence victims suffer health impact both physically and psychologically. Physically, they are experiencing bruises, swelling, up to stitches on the part of their body. While psychologically, they feel common to deep fear, cannot sleep well, feel insecure to experience trauma. As the impact of reproductive health, the victim suffered miscarriage. The victims are needed assistance to be brave enough to speak up and seek protection quickly and accurately.